Driving Repurchase Intention in E-Commerce: The Synergistic Role of Promotional Innovation and User Experience among Lazada Consumers - Tambunan, Debora; Mega Hernawati Harefa; M Chandra Wibowo; Dini Vientiany; Affendy Abu Hassim (Yayasan Bina Bisnis Nusantara Medan, 2025)
This study is to examine the impact of promotional innovation and user experience on the repurchase intentions of Lazada consumers in Medan City, both individually and collectively. This study also aims to enhance comprehension of how new advertising techniques and gratifying user experiences might augment consumer loyalty in the digital marketplace. The methodology employed is quantitative, utilizing a survey technique. Data were gathered from 200 Lazada users in Medan City, chosen through purposive sampling based on the criterion of having shopped at Lazada multiple times and being residents of Medan. The Partial Least Squares–Structural Equation Modeling (PLS-SEM) method was used to analyze the data and examine the association between the research variables. SmartPLS 4.0 software was used to do this. The data shows that both promotional innovation and user experience have a favorable and significant effect on the intention to buy again, both on their own and together. This analysis shows that good user experiences and inventive marketing methods are important for getting people to buy again and making them more loyal. This study enhances the digital marketing literature by elucidating the synergistic impact of promotional innovation and user experience on consumer repurchase intention, specifically within the realm of e-commerce in Indonesia. These findings underscore the necessity for e-commerce entities such as Lazada to cultivate creative promotional techniques and enhance the user experience to foster enduring consumer loyalty and bolster competitiveness in the digital age. This study was limited to Lazada customers in Medan City; hence, the findings may not be applicable to other regions or e-commerce platforms with distinct consumer demographics